Sparking Entrepreneurial Tendencies in Youth: Lessons From Sport and Life Skills Education in Three African Cities - McCole, D.; Malete, L.; Tshube, T.; Mphela, T.; Maro, C.; Adamba, C.; Machuve, J.; Ocansey, R. (Gateways: International Journal of Community Research and Engagement, 2022)
This practice-based article describes a program that aims to instil an interest in entrepreneurship among African youth by helping them make a connection between the skills they have developed through their participation in sport and the skills required of successful entrepreneurs. The program was developed in partnership between scholars at four universities (University of Botswana, University of Dar es Salaam, University of Ghana and Michigan State University), as well as schools at other community organisations in three African cities: Gaborone, Botswana; Dar es Salaam, Tanzania; and Accra, Ghana. The program, which seeks to contribute to the well-established need for job creation in sub Saharan Africa, integrated basic entrepreneurship and life-skills training activities into a sports camp for youth athletes. The program appears to have developed entrepreneurial tendencies among youth sport participants in these African cities, suggesting that job creation efforts could benefit from targeting youth sport participants and helping them to recognise the important skills they have developed through their participation in sport, and helping them to identify ways in which that skill development could positively impact their futures.
Research Article
Keywords: Entrepreneurship; Job Creation; Sport; Youth Sport; Youth Development; Africa